Retórica y libros de caballerías. La presencia de exempla en la Rhetorica cristiana de Diego Valadés - Chaparro Gómez, César (Cuadernos de Filología Clásica. Estudios Latinos, 2004)
The even more thorough knowledge we have of Diego Valadés and bis rhetorica christiana leads us, as it is the case, to the discovery of unsuspected relationships between authors and genres. In more specific terms, this paper reveals the relationship between a peculiar Romance of Chivalry, Femando Basurtos Don Florindo, and sorne exempla contributed by the Franciscan rhetor in his rhetoric treatise.